BIOSAFETY AND MANAGEMENT OF SOLID WASTE FROM HEALTH SERVICES (Fiep Bulletin - online, 2019)
Introduction: The problems involving the management and biosecurity of solid waste from health services (SSR),formerly called hospital waste, are diverse and comprehensive, so we'll focus only on three topics of relevance: the use of PPE ofindividual protection), the classification of these RSS, and the form of management. Objective: To approach the problems relatedto incorrect handling and lack of biosafety related to SSR, with the specific objectives of: highlighting the use of PPE for the safetyof professionals, improving knowledge about SSR classification, and relevance of proper handling. Method: Characterized asnarrative literature review, with theoretical reference taken from virtual databases (Scielo and BDNEF), projects and scientificarticles, ordinances and resolutions referenced thematic: Biosafety, Handling, Solid Waste Health Service, Work safety. Resultsand Discussion: Keep professionals always up to date on standards, routines, classification, handling, as well as biosafetymeasures, thus minimizing possible work accidents. Conclusion: It is important to idealize the focus of the research, to improvethe knowledge of the professionals of garbage collection regarding biosafety in their workplaces and also to point out theproblems of the inadequate management of the solid residues of health services and the damages caused to the health of theworkers , that behavioral attitudes be rethought, thus avoiding future harm to their health.